A Lysosome‐Targeted Magnetic Nanotorquer Mechanically Triggers Ferroptosis for Breast Cancer Treatment - Xueyan Wei; Yingze Li; Haotian Chen; Rui Gao; Peng Ning; Yingying Wang; Wanxin Huang; Erzhen Chen; Lan Fang; Xingrong Guo; Cheng Lv; Yu Cheng (Advanced Science, 2024)
Abstract Targeting ferroptosis has attracted exponential attention to eradicate cancer cells with high iron‐dependent growth. Increasing the level of intracellular labile iron pool via small molecules and iron‐containing nanomaterials is an effective approach to induce ferroptosis but often faces insufficient efficacy due to the fast drug metabolism and toxicity issues on normal tissues. Therefore, developing a long‐acting and selective approach to regulate ferroptosis is highly demanded in cancer treatment. Herein, a lysosome‐targeted magnetic nanotorquer (T7‐MNT) is proposed as the mechanical tool to dynamically induce the endogenous Fe2+ pool outbreak for ferroptosis of breast cancer. T7‐MNTs target lysosomes via the transferrin receptor‐mediated endocytosis in breast cancer cells. Under the programmed rotating magnetic field, T7‐MNTs generate torques to trigger endogenous Fe2+ release by disrupting the lysosomal membrane. This magneto‐mechanical manipulation can induce oxidative damage and antioxidant defense imbalance to boost frequency‐ and time‐dependent lipid peroxidization. Importantly, in vivo studies show that T7‐MNTs can efficiently trigger ferroptosis under the magnetic field and play as a long‐acting physical inducer to boost ferrotherapy efficacy in combination with RSL3. It is anticipated that this dynamic targeted strategy can be coupled with current ferroptosis inducers to achieve enhanced efficacy and inspire the design of mechanical‐based ferroptosis inducers for cancer treatment.